THE DEVELOPMENT OF PROBLEM BASED LEARNING (PBL) MODELS BASED ON BATAK CULTURE TO INCREASE SKILL STUDY RESOLUTION - Annisyah Lubis; Mara Bangun Harahap; Derlina Nst; Sahyar Sahyar; Bornok Sinaga (Universitas Negeri Medan, 2018)
This study aims to determine: the effectiveness of the development of problem based learning model based on Batak culture implemented in learning tools developed, improvement of problem solving skills of physics that dibelajarkan with model based learning based on batak culture. Type of research is development (development of research) by using model of development of Thiagaraian, Semmel and Semmel that is 4-D model (four D Model). The sample in the study is one class X of all classes of MIA X present in the research site. The instrument used is a problem-solving test. Data in the study were analyzed using N-gani. The results showed that: the effectiveness of learning tools through the model based learning based on Batak culture in improving the ability of problem solving physics has been able to be said to be effective for use in learning, there is improvement of problem solving problems of physics students using learning tools based on culture based Batak on measurement material